Morphology and molecular phylogeny of Dothideomycetes fungi associated with Dracaena plants - Chaiwan, Napalai; Hyde, Kevin David; Jayawardena, Ruvishika Shehali; Tibpromma, Saowaluck; Wanasinghe, Dhanushka N.; Manawasinghe, Ishara Sandeepani; Manamgoda, Dimuthu S.; Promputtha, Itthayakorn (Frontiers in Cellular and Infection Microbiology, 2025)
Dracaena species are widely recognized for their exceptional drought tolerance, making them ideal candidates for sustainable landscaping and ecological restoration in arid regions. Limestone outcrops hosting Dracaena are unique ecosystems characterized by extreme environmental conditions such as nutrient-poor substrates. Thus, they provide valuable opportunities for studying fungal diversity and their adaptations. Despite their ecological importance, knowledge concerning fungal communities associated with limestone-inhabiting Dracaena species remains limited, particularly within the diverse biogeographic contexts of Thailand. Microfungal samples were collected from dead wood and leaves of Dracaena species across seven provinces in Thailand (Chiang Rai, Kanchanaburi, Krabi, Nakhon Si Thammarat, Ratchaburi, Songkhla, and Tak). Fungal taxa were identified and characterized through detailed morphological examinations combined with multi-gene phylogenetic analyses using Actin (act), Internal transcribed spacer (ITS), the large subunit of nuclear ribosomal RNA (LSU), translation elongation fac-tor 1-alpha (tef1-α), and beta-tubulin (tub) gene regions. This study documents eleven fungal taxa isolated from Dracaena substrates, belonging to seven families across five fungal orders. Three new species viz. Cladosporium dracaenae, C. dracaenicola and Torula dracaenae were described, and eight new host records were established (Bipolaris coffeana, Curvularia lunata, Lasiodiplodia bruguierae, L. lignicola, L. thailandica, Longididymella clematidis, Ochroconis musae and Zasmidium citrigriseum). Species de-scriptions, color photographic plates, phylogenetic trees and updated taxonomic notes are provided for all isolated taxa. The findings advance the current understanding of microfungal diversity associated with limestone outcrop habitats and Dracaena species, contributing to broader ecological and conservation efforts. By revealing novel fungal species and previously undocumented host-fungus interactions, this study underscores the rich but underexplored fungal biodiversity of limestone ecosystems in Thailand.